Publishing e-books for dummies - Luke, Ali. (Hoboken, NJ : John Wiley & Sons, Inc., 2012)
There's more to publishing an e-book than you might think-- and this guide explains it all! E-books give you full control: you no longer need to go through agents or publishers. But you do need to know about writing, publishing, and promoting an e-book in order to put it in front of a worldwide audience.
Introduction -- Getting to know e-books -- Creating your e-book -- Creating your website -- Selling your e-book -- Marketing your e-book -- The part of tens.
Includes bibliographical references and index.
Keywords: Self-publishing.; Electronic publishing